Haematological and biochemical reference intervals for three species of hydrophiine sea snakes (Hydrophis curtus, H. elegans and H. peronii) in Australia. Issue 3 (June 2015) - Gillett, Amber K.; Flint, Mark; Hulse, Lyndal; Hanger, Jon; Mills, Paul C.
Highlights Haematological and biochemical reference intervals are provided for three species of Hydrophiine sea snakes. Reference intervals can be used to assess health in sea snakes. Lymph contamination is minimised by modifying blood collection methods. Most haematological and biochemical parameters are unaffected by lymph contamination.